1974
DOI: 10.3758/bf03333035
|View full text |Cite
|
Sign up to set email alerts
|

Bait-shyness acquisition and resistance to extinction as functions of US exposure prior to conditioning

Abstract: Cyclophosphamide-induced aversions to saccharin-flavored tap water were observed in normal control rats, in rats subjected to varying numbers of cyclophosphamide injections prior to conditioning, and in rats similarly subjected to preconditioning saline injections. Both initial magnitude and resistance to extinction of a conditioned flavor aversion were found to be inverse functions of preconditioning familiarity with drug-induced illness. Six preconditioning cyclophosphamide injections markedly reduced both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 13 publications
2
29
1
Order By: Relevance
“…Further, habituation may not only reduce unconditioned suppression to a stimulus, but rnay also block conditioning to it in a manner similar to preexposure to the CS (Lubow, 1965). Results of Experiment 1, in which a conditioned aversion to saccharin was blocked by three preconditioning LiCl intubations, support similar results by Brookshire and Brackbill (Note 1) and Elkins (1974). In both of these studies, an inverse relation was found between the frequency of the preconditioning exposure to toxie illness and the initial magnitude of the aversion.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Further, habituation may not only reduce unconditioned suppression to a stimulus, but rnay also block conditioning to it in a manner similar to preexposure to the CS (Lubow, 1965). Results of Experiment 1, in which a conditioned aversion to saccharin was blocked by three preconditioning LiCl intubations, support similar results by Brookshire and Brackbill (Note 1) and Elkins (1974). In both of these studies, an inverse relation was found between the frequency of the preconditioning exposure to toxie illness and the initial magnitude of the aversion.…”
Section: Discussionsupporting
confidence: 77%
“…An interesting difference between the results of the present study and that of Elkins (1974) concerns the degree of attenuation of the learned association following preconditioning habituation to the USo Elkins reported that, following six preconditioning cyclophosphamide injections, a learned aversion to saccharin was formed whieh lasted at least 10 days before extinguishing, while the present study revealed no aversion to saccharin following only five preconditioning LiCI intubations. It is probable that these conflicting results are due to differences in the toxins used.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Kremer (1971), Rescorla (1973), andSiegel and Domjan (1971) found that habituation to shock or loud noise attenuated the ability of a stimulus subsequently paired with the shock or noise to suppress barpressing for food. In the experiments of Brackbill (1971, 1976), Cannon, Berman, Baker, and Atkinson (1975), Elkins (1974), and LeBlanc and Cappell (1974), habituation to apomorphine, ethanol, lithium chloride (LiCl), cyclophosphamide, morphine, or amphetamine reduced the subsequent efficacy of these drugs in reinforcing aversions to saccharin.Habituation to the reinforcer after learning, however, mayor may not reduce the conditioned responses shown in a subsequent test. When Rescorla (1973) habituated rats to a loud noise after pairing the noise with a light, the habituation hastened later extinction of conditioned suppression in the light.…”
mentioning
confidence: 99%